Assessment Of Prevalence of Diabetes Among Rural Population of Pune District, India - Kundap, Ritesh P; Vidhate, Kshama B; Fernandez, Kevin (National Journal of Community Medicine, 2015)
Introduction: Diabetes is the commonest non-communicable dis- ease in India with its onset almost a decade earlier as compared to developed countries. The proportion of people with diabetes is in- creasing very fast in India. Increased longevity and susceptibility of Indians to premature onset of DM have been the important rea- sons for this change. Objective of the study was to assess the prev- alence of diabetes and associated risk factors in rural population using a simple diagnostic tool. Method: A cross sectional survey was done in one randomly se- lected village of rural field practise area of a medical college in Pune district. House to house visits were paid and 255 residents of 20 and above years of age were interviewed using Indian diabetes risk score (IDRS). Those who screened positive on the score were tested for fasting blood sugar by Glucometer method. Results: The prevalence of diabetes among the study population was 10.5%. Among the 27 newly detected cases 18 had high risk and 9 had moderate risk on IDRS. The statistically significant risk factors were age, non-vegetarian diet, socio economic status and body mass index. Conclusion: The prevalence diabetes has started increasing in poor, illiterate and health ignorant rural population. They should be diagnosed at the earliest possible time using simple diagnostic tools like IDRS.